AN EFFICIENT PROTOCOL FOR IN VITRO MASS PROPAGATION OF FUSARIUM WILT RESISTANT CASTOR (RICINUS COMMUNIS L.) PARENTAL LINE SKP-84 THROUGH APICAL MERISTEM - R. V. KANSARA,; SANJAY JHA,; JHA, SUMAN KUMAR; M. K. MAHATMA, (The Bioscan, 2013)
Successful in vitro plant regeneration protocol has been described for fusarium wilt resistant castor (Ricinus communis L.) parental line SKP-84 through apical meristem. Shoot apex containing apical meristems, were excised from 5-7 days old in vitro grown seedlings and cultured on Murashige and Skoog (MS) medium supplemented with various concentrations of cytokinins either alone or in combination. Kinetin had marked effect on shoot initiation and shoot quality. Kinetin (2.325µM) in combination with BAP (1.111µM) produced maximum number of shoot (10.33) and shoot length (5.20 cm). In vitro produced shoots were transferred to rooting media containing half strength MS basal media supplemented with NAA at various concentrations. Well developed roots appeared in media supplemented with 0.537µM NAA (69.00 %). Rooted plants were transferred to the pots containing vermicompost with 64.5% survival rate in hardeninng. No genetic variation was detected in plantlets as revealed by RAPD at different stages proved the genetically stability during in vitro plant regeneration through apical meristem culture.